Synthetic Studies on Enantioselective Total Synthesis of Cyathane Diterpenoids: Cyrneines A and B, Glaucopine C, and (+)-Allocyathin B2 - Wu, Guo-Jie; Zhang, Yuan-He; Tan, Dong-Xing; He, Long; Cao, Bao-Chen; He, Yu-Peng; Han, Fu-She (Journal of organic chemistry, 2019)
The details for the synthetic studies on enantioselective total synthesis of cyathane diterpenoids cyrneine A (1) and B (2), glaucopine C (3), and (+)-allocyathin B2 are presented. We established a mild Suzuki coupling for heavily substituted nonactivated cyclopentenyl triflates using a phosphinamide-derived palladacycle as precatalyst and a chelation-controlled highly regioselective Friedel–Crafts cyclization. The utilization of these two key reactions enabled a rapid construction of the 5-6-6 tricyclic skeleton. In the middle stage of the synthesis, a Birch reductive methylation, a modified Wolff–Kishner–Huang reduction, and a carbenoid-mediated ring expansion were employed as the key reactions to furnish the 5-6-7 tricyclic core bearing two antiorientated all-carbon quaternary stereocenters at the C6 and C9 ring junctions. By applying these key transformations, a more efficient total synthesis of cyrneine A and allocyathin B2, and the first total synthesis of cyrneine B and glaucopine C, were accomplished through a collective manner. The late-stage conversions involving a base-mediated double bond migration and a double bond migration/aerobic γ-CH oxidation cascade for the stereoselective synthesis of cyrneine B and glaucopine C were interesting.